The arts legacy of the Franciscan Order in the city of São José/SC: Beauty for the apostolate (Palíndromo, 2025)
The aim is to analyze the legacy of the arts of the Franciscan Order in the Parish of São José/SC between 1904 and 1967, considering in addition to the artistic instance, the historical and apostolic instances and relating them to the Josephan identity. The specific objective is: to identify and characterize the historical, artistic and apostolate contributions to the Mother Church during the Franciscan administration; point out the permanence and transformations in material goods that promote art as a means of communicating Sacred Truths; and promote the preservation of Christian religious heritage in the contemporary city. Such analysis is based on the communicative premise of sacred art and architecture in the dissemination of the dogmas of the Catholic faith, through the mystagogical potential. Furthermore, the Pontifical Commission for the Cultural Assets of the Church works to safeguard the testimony of Christ among men, including the evangelizing activity of Communities of Consecrated Life. When carrying out qualitative research, the hypothetical-deductive method was adopted, including indirect and direct documentary collection based on the examination of sources and bibliography, on-site survey, photographic records and interviews. The hypothesis is defended and confirmed that the legacies of the Parish of São José are vivid traces of the pastoral work of the Franciscan Order, which articulated the community and promoted the Christian world in Santa Catarina lands for six decades.
Keywords: Visual arts; beauty; cultural heritage; Order of Saint Francis; Saint Joseph (SC).